Determinants of women’s entrepreneurial performance in Kerala - Bonny, Binoo P; Lokesh, S.; Smitha, S. (Indian Journal of Extension Education, 2021)
Women entrepreneurs have a significant impact on the economic development in global as well as national context. Capacitating women with entrepreneurial qualities has remained key to social transformation especially in developing countries. The paper presents the results of a study conducted in Kerala during 2020-21 to analyse the determinants of women’s entrepreneurial performance related to agricultural enterprises. Seventy women entrepreneurs involved in agricultural ventures randomly selected from the 14 districts of Kerala formed the study sample. Analysis of data collected based on a pretested structured interview schedule indicated mushroom and value addition enterprises as the most successful enterprises among women.Â It was estimated that these enterprises took three and six months, respectively and production levels of 1872 kg and 1462 kg each in order to reach break-even points. Mass media contact and stage of enterprise were the factors which were delineated as the factors that contributed significantly to the period taken to achieve the break-even point by the women-led enterprises.